2010
DOI: 10.1021/jm901741p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Acridone Derivatives, Inhibitors of NS3 Helicase, Which Efficiently and Specifically Inhibit Subgenomic HCV Replication

Abstract: A new goup of acridone derivatives, obtained by reaction of acridone-4-carboxylic acid derivatives with aromatic amines, was tested to determine the inhibitory properties toward the NS3 helicase of hepatitis C virus (HCV). Six compounds inhibited the NS3 helicase at low concentrations (IC(50) from 1.5 to 20 microM). The acridone derivatives probably act via intercalation into double-stranded nucleic acids with a strong specificity for double-stranded RNA, although an interaction with the enzyme cannot be exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 32 publications
0
43
0
Order By: Relevance
“…This 170 could be explained by the way acridones usually act against virus infection. Some authors argue 171 that their nucleic acid intercalation ability and interaction with viral enzymes are the main 172 mechanisms by which these compounds act (Adams, 2002;Stankiewicz-Drogon et al, 2010;workers (Stankiewicz-Drogon et al, 2010;Stankiewicz-Drogon et al, 2008) reinforces this 175 assumption. Acridones showed inhibition of NS3 helicase, T7 RNA polymerase (topology and 176 function similar to HCV NS5B) and strong double-stranded RNA intercalation property.…”
Section: Discussion 150mentioning
confidence: 99%
See 3 more Smart Citations
“…This 170 could be explained by the way acridones usually act against virus infection. Some authors argue 171 that their nucleic acid intercalation ability and interaction with viral enzymes are the main 172 mechanisms by which these compounds act (Adams, 2002;Stankiewicz-Drogon et al, 2010;workers (Stankiewicz-Drogon et al, 2010;Stankiewicz-Drogon et al, 2008) reinforces this 175 assumption. Acridones showed inhibition of NS3 helicase, T7 RNA polymerase (topology and 176 function similar to HCV NS5B) and strong double-stranded RNA intercalation property.…”
Section: Discussion 150mentioning
confidence: 99%
“…Some acridones from Rutaceae plants showed great 153 antiviral activity against viruses with DNA genomes like herpes simplex virus serotypes 1 and 2 154 (HSV-1 and HSV-2), human cytomegalovirus (HCMV) and Epstein-Barr virus (Chansriniyom et 155 al., 2009;Itoigawa et al, 2003;Takemura et al, 1995;Yamamoto et al, 1989). For RNA 156 viruses, acridones presented activity against HIV-1, bovine viral diarrhea virus (BVDV), all 157 serotypes of dengue virus (DENV) and HCV, the last three belonging to the Flaviviridae family 158 (Fujiwara et al, 1999;Houe, 2003;Mazzucco et al, 2015;Raney et al, 2010;Sepulveda et al, 159 2008;Stankiewicz-Drogon et al, 2010;Stankiewicz-Drogon et al, 2008;Tabarrini et al, 2006;160 Turpin et al, 1998). 161 Our results showed that Fac4 inhibited up to 92% of HCV replication in the context of either the 162 subgenomic replicon or full length JFH1 HCVcc.…”
Section: Discussion 150mentioning
confidence: 99%
See 2 more Smart Citations
“…There are numerous functions of the acridone nucleus in addition to its derivatives that have been reported in previous studies, including anticancer (13-16), anti-herpes (17), anti-malarial (18,19), antivirus (20), anti-allergy (21) and anti-leishmanial (22) activities. These features are attributed to the semi planar heterocyclic structure, which interacts with different biomolecular targets.…”
Section: Discussionmentioning
confidence: 98%